2021
DOI: 10.1093/jxb/erab396
|View full text |Cite
|
Sign up to set email alerts
|

OsbZIP62/OsFD7, a functional ortholog of FLOWERING LOCUS D, regulates floral transition and panicle development in rice

Abstract: We have characterized a rice bZIP protein coding gene OsbZIP62/OsFD7 that expresses preferentially in SAM and during early panicle developmental stages in comparison to other OsFDs characterised to date. Surprisingly, unlike OsFD1, OsFD7 interacts directly and more efficiently with OsFTLs; the interaction is strongest with OsFTL1 followed by Hd3a and RFT1, as confirmed by FLIM-FRET analysis. Also, OsFD7 is phosphorylated at its C-terminal end by OsCDPK41 and OsCDPK49 in vitro and this phosphorylated moiety is … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…For example, Zm00001d023424 encodes the bZIP transcription factor, and Zm00001d047250 encodes the PLATZ transcription factor. In rice, OsbZIP62 , which is a functional orthologue of FLOWERING LOCUS D, regulates the floral transition and panicle development ( Kaur et al., 2021 ). In grapevine, VviPLATZ1 is a major factor that controls female flower morphology determination ( Iocco-Corena et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Zm00001d023424 encodes the bZIP transcription factor, and Zm00001d047250 encodes the PLATZ transcription factor. In rice, OsbZIP62 , which is a functional orthologue of FLOWERING LOCUS D, regulates the floral transition and panicle development ( Kaur et al., 2021 ). In grapevine, VviPLATZ1 is a major factor that controls female flower morphology determination ( Iocco-Corena et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The structure of the FAC was first shown to contain the OsFD1 transcription factor, but it was later demonstrated that several bZIPs can replace OsFD1 ( Tsuji et al., 2013 ; Brambilla et al., 2017 ; Jang et al., 2017 ; Cerise et al., 2021 ; Kaur et al., 2021 ). bZIPs act as dimers, and the complex orients their DNA-binding domain towards the DNA.…”
Section: The Response Of the Sam To Flowering Inductive Signalsmentioning
confidence: 99%
“…Thus, OsCIPK3 specifically affects the assembly of an RFT1/14-3-3/OsFD1 complex under LDs, suggesting that another unknown kinase operates under SDs. The calcium-dependent protein kinases OsCDPK41 and OsCDPK49 interact with and phosphorylate OsFD7, which forms FACs with Hd3a and RFT1 as well as with FT-L1 ( Kaur et al., 2021 ). The phenotypic consequences of their mutation have not yet been determined, but they could be good candidates contributing to bZIP phosphorylation under SDs.…”
Section: The Response Of the Sam To Flowering Inductive Signalsmentioning
confidence: 99%
“…Additionally, FLIM is largely independent of protein concentration. Therefore, FRET-FLIM measurements are widely considered as more reliable than the detection of FRET by APB and spectral imaging, and have been successfully applied in planta ( Stahl et al , 2013 ; Bücherl et al , 2014 ; Somssich et al , 2015 ; Long et al , 2017 ; Weidtkamp-Peters and Stahl, 2017 ; Betegón-Putze et al , 2021 ; Kaur et al , 2021 ).…”
Section: Measurement Of Ppi By Energy Transfermentioning
confidence: 99%